Pengaruh PAD, SiIPA, dan Fiscal Stress terhadap Perubahan Belanja Bantuan Sosial pada Pemerintah Daerah - Muhammad Nur Rafli; Vita Fitria Sari (Universitas Negeri Padang, 2021)
The objective of this study is to determine the effect of of local revenue budgets (PAD), time over budget calculation (SiLPA), and fiscal stress to budget social assistance expenditure changes on local government in Sumatra. The sampling technique used is purposive sampling. The sample of this study using 51 districts/cities in Sumatra Island period of 2016-2019. The type of data used secondary data obtained from from local government financial report (LKPD) and the website of DJPK Kemenkeu RI. The analytical method used is panel regression. The results of regression testing showed that only rebudgeting in SiLPA which effect positive and significant to budget expenditure change, while local revenue budgets (PAD) and fiscal stress does not significantly effect to budget social assistance expenditure changes on local government in Sumatra of 2016-2019.